Collaborating for food security in Ethiopia - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
IFPRI’s long-term collaboration with the government and research institutions in Ethiopia has provided the foundation for a strong knowledge base for the rural sector, incorporation of research evidence into policymaking, and development of effective institutions to promote agricultural productivity and support rural populations.